Friendly bureaucrats, formal rules and firms' investment decisions: evidence from a survey experiment in Russia. Issue 2 (3rd September 2020) - Yakovlev, Andrei; Ivanov, Denis
Abstract : Purpose: The purpose of this paper is to investigate the links between investment activity and personal contacts for small- and medium-sized firms with public officials at the subnational level in Russia. Design/methodology/approach: A list-experiment design, using a survey of 21, 000 Russian firms in 2017, was used to evaluate the importance of personal connections with officials for conducting business. Findings: A total of 27% of firms without investment and 37% with investment considered personal connections with officials an important factor for doing business. The importance of such contacts was lower in regions with a better investment climate. However, a higher proportion of firms were likely to invest in the regions where higher importance was placed on political connections. Therefore, in Russia in the mid-2010s, investment from politically connected firms did not crowd out investment from other firms. Research limitations/implications: Although the available data did not allow causality to be defined, the research shows that political connections are important for investors in emerging markets and that the importance of political connections diminishes with improvement in the business climate. Originality/value: This paper provides a quantitative estimate of the relationship between political connections and firm investment in Russia, an example of large emerging economy. This relationship is moderated by institutional quality at the subnational level. The results provide empirical support for the theory of limited access orders elaborated by North et al. (2009), and stress the importance of rents and their productive utilization for the development of emerging economies.